The Influence of The Problem-Based Learning (PBL) Model on Critical Thinking Ability in History Learning at Senior High School - Rohimah, Rohimah; Setiawati, Elis; Afwan, Bahtiar; Putra, Agung Dian; Meihan, Andre Mustofa (Swarnadwipa, 2025)
This research aims to determine the effect of applying the Problem Based Learning (PBL) learning model on critical thinking skills in history learning. This research was carried out at State Senior High School (SMA Negeri) 1 Gunung Sugih in February, even semester of the 2023/2024 academic year. The research method used in this research is quasi-experimental. The research sample consisted of 31 students each in the control and experimental classes. The data collection technique used was an Essay Test in the form of 10 questions which were then analyzed using the t test. The results of hypothesis testing using SPSS version 22 software obtained Sig data <α, namely 0.000 <0.05 so that H0 was rejected and H1 was accepted. This shows that there is an influence of the Problem Based Learning (PBL) learning model on critical thinking skills in history learning.